Statistical analysis of the occupational radiation doses in three different positron emission tomography–computed tomography centers in Egypt - Ibrahim Elsayed Saad Ahmed; Abdulrahman M.M. Zamzam; Hossam Mahmoud Yassin (World Journal of Nuclear Medicine)
In the present study, we investigated the radiation doses received by the positron emission tomography (PET)/computed tomography (CT) staff in three different diagnostic centers in Egypt. The whole-body effective dose measured by thermoluminescent dosimeters (TLDs) for staff working in PET and the effective dose per study received by physicist, technician, and nurse were measured by an electronic pocket dosimeter (EPD) during a period of 6 months. Statistical analysis was held between the measurements of the TLDs as well as for the EPD for the three studied PET-CT centers. After combining TLD and EPD prospective annual scores for the three studied categories in the three centers, the one-way ANOVA test results have shown that there were statistically significant differences between group means with respect to their TLD mean score (P = 0.041). The mean nurse group TLD score, across the three centers, appeared to be the lowest scoring 3.83 (standard deviation [SD] 0.012) compared to the physicist and technician who measured 4.62 (SD 0.231) and 6.92 (SD 0.018), respectively. Scheffe's test for complex comparisons revealed a significant difference between nurse group and technologist group (P = 0.001). Regarding the annual combined EPD scores, the post hoc test, namely Scheffe's test for complex comparisons, revealed a significant difference between nurse group and technologist group (P = 0.001). This was measured after the one-way ANOVA test results have shown that there were statistically significant differences between annual group EPD means (P = 0.032). Finally, there was no recorded significance for the studied categories across the three centers between their annual TLD and EPD dose scores (P = 0.072). Technicians group received the highest mean effective whole-body doses when compared with the International Commission on Radiological Protection dose limit, each individual worker can work with many more 18F-fluorodeoxyglucose (FDG) PET/CT studies for a (period time) without exceeding the occupational dose limits if the average received effective dose continues with the same rate. The study also confirmed that low levels of radiation dose are received by medical personnel involved in 18F-FDG PET/CT procedures in those centers due to implementing radiation protection measures and procedures.